Preparation of Highly Monodisperse Electroactive Pollen Biocomposites - Seo, Jeongeun (2016)
Sunflower pollen (SFP) was used as a novel biotemplate to fabricate nanoporous and spiked particles coated with carboxyl-functionalized multiwalled carbon nanotubes (COOH-MWCNTs). The MWCNT coating on SFPs was characterized by scanning electron microscopy, dynamic imaging particle analysis and Raman spectroscopy. The electrical properties of MWCNT-coated SFPs offer great potential to develop highly functional materials for electronics and optical applications.